Arctic warming interrupts the Transpolar Drift and affects long-range transport of sea ice and ice-rafted matter - Krumpen, Thomas; Belter, H. Jakob; Boetius, Antje; Damm, Ellen; Haas, Christian; Hendricks, Stefan; Nicolaus, Marcel; Nöthig, Eva-Maria; Paul, Stephan; Peeken, Ilka; Ricker, Robert; Stein, Rüdiger (Scientific reports, 2019)
Sea ice is an important transport vehicle for gaseous, dissolved and particulate matter in the Arctic Ocean. Due to the recently observed acceleration in sea ice drift, it has been assumed that more matter is advected by the Transpolar Drift from shallow shelf waters to the central Arctic Ocean and beyond. However, this study provides first evidence that intensified melt in the marginal zones of the Arctic Ocean interrupts the transarctic conveyor belt and has led to a reduction of the survival rates of sea ice exported from the shallow Siberian shelves (−15% per decade). As a consequence, less and less ice formed in shallow water areas (<30 m) has reached Fram Strait (−17% per decade), and more ice and ice-rafted material is released in the northern Laptev Sea and central Arctic Ocean. Decreasing survival rates of first-year ice are visible all along the Russian shelves, but significant only in the Kara Sea, East Siberian Sea and western Laptev Sea. Identified changes affect biogeochemical fluxes and ecological processes in the central Arctic: A reduced long-range transport of sea ice alters transport and redistribution of climate relevant gases, and increases accumulation of sediments and contaminates in the central Arctic Ocean, with consequences for primary production, and the biodiversity of the Arctic Ocean.